Over a million students use our free study notes to help them with their homework
The first step that we need to take is to take all the 'x' terms to one side of the inequality. In this case, we can subtract '3x' from both sides to obtain 2x+3 ≤ -6. Then we want to take all the non- x ...
a) This question tests you on using fractions, brackets and quadratic equations. We should start by trying to make it into a form we know how to deal with. This will be by the balance method. If we multi...
Multiply by 4-y => t(4-y)=y+2 Expand the brackets => 4t-ty=y+2 Get all the y's on the same side => 4t-2=ty+y Factor out the y => 4t-2=(t+1)y Divide by t+1 => (4t-2)/(t+1)=y
5x +3 > 3x -6 2x +3 > -6 (-3x from both sides) 2x > -9 (-3 from both sides) x > -4.5 (divide by two on both sides)
First of all we need to get all of the x's on one side and all the numbers on the other side. Therefore to do this firstly we should add 2 to both sides. 8x > 4x +8 Secondly we need to -4x from both si...
←
657
658
659
660
661
→
Internet Safety
Payment Security
Cyber
Essentials